Categorical Imperative in the Ethics of Kant - Kuzmickas, Bronislavas (Problemos, 1974)
The seminar devoted to the 250th anniversary of I. Kant’s birth was held on the 17th of April 1974 in Vilnius University. Some of the addresses read at the seminar are published in this issue. B. Kuzmickas deals with the categorical imperative in the ethics of Kant.